Intermittent catheterization: A patient-centric approach is key to optimal management of neurogenic lower urinary tract dysfunction - Krassioukov, Andrei; Welk, Blayne; Vrijens, Desiree; Islamoska, Sabrina; Barken, Kim Bundvig; Keppenne, Veronique; Wyndaele, Michel; Walter, Matthias (Frontiers in Urology, 2023)
The value of disposable, single-use catheters has come under scrutiny in recent years with a growing attention on environmental sustainability. Intermittent catheterization (IC) is a widely available and minimally invasive technique for management of lower urinary tract dysfunction. Effective IC for individuals with neurogenic lower urinary tract dysfunction can promote their independence and improve quality of life. Are there alternative options within IC that could minimize environmental impact without compromising the safety and effectiveness of single-use catheters? How does the future of IC look – environmentally friendly, biodegradable, disposable catheters may be complementary to certified reusable catheters? In the midst of this debate, it is important to emphasize that individuals have the right to choose the best evidence-based treatment available. Here we consider the current landscape for IC with a focus on chronic use in individuals with neurogenic lower urinary tract dysfunction.